Cyber activism in the Middle East: Pre and Post of Arab Spring / Rafidah Mohd Azli - Mohd Azli, Rafidah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2018)
Cyber activism played a vital role to muzzle the conventional media in the Middle East and a number of the developing countries. According to the Eltantawy and Wiest (2011), by using the new media such as new communication of social media, the collective activities can be implemented, the collective identity among the marginalized group members can be promoted, political spaces is created and connections among other social move- ments is established. Antiwar, anti- globalization and global justice become the prominent of cyber activism. Furthermore, the new media is an additional resource for social movements implemented by the “resource poor" actors. It also interpreted the means of the constraints of financial, temporal or spatial among the mass communication. In the case of Egypt, the United Nations Development Programme s 2008 annual report, about 20% of the Egyptian population then lived below the poverty line and it was becoming increasingly challenging for Egypt’s poor to satisfy basic needs Eltantawy and Wiest (2011). These conditions gradually strengthen public trustration and Irritation with the regime, which appeared to be enduring, as Hosni Mubarak was coaching his son Gamal to succeed him.